THE INFLUENCE OF PROBLEM BASED LEARNING MODEL WITH KEY RELATION CHART MEDIA TOWARD CRITICAL THINKING AND STUDENT’S GROUP COOPERATION IN CLASS VIII SMP NEGERI 14 SURAKARTA ACADEMIC YEAR 2012/2013 - Suciati, Ari Tyas Susanti,Baskoro Adi P (Pendidikan Biologi, 2015)
The purposes of this research are to know the influence of problem based learning model with key relation chart media toward the student?s critical thinking and group cooperation in VIII class of SMP Negeri 14 Surakarta Academic Year 2012/2013. This research was quasi experimental research with post-test non equivalent control croup design and cluster sampling technique. The population of this research was all students in VIII class of SMP Negeri 14 Surakarta Academic Year 2012/2013, the sample was two classes, they are experiment class used problem based learning model with key relation chart media and control class with convensional model, that is variative speech learning model with simple chart. Data collection technique was with essay test, cooperation observation sheet, questionnaire of cooperation, and student?s early value documentation. Based on hypothesis test result with t test, it has obtained  t count value, that are 2,169 and sig. are 0,037 for student?s group cooperation value. Sig?s value from two t test for critical thinking variable and student?s group cooperation were bigger than 0,05, so Ho was denied. It has showed that critical thinking and student?s group cooperation in experiment and control class was really different. The result of  data analysis above proof  that there was an influence of problem based learning model with key relation chart media toward critical thinking and student?s group cooperation in VIII class of SMP Negeri 14 Surakarta Academic Year 2012/2013. Keywords: problem based learning model, key relation chart media,critical thinking, group cooperation.